Odpowiedzi

2009-10-05T18:32:22+02:00
A) log a3 + log a4 - log a2 a-podstawa logarytmowana

log_a(3) + log_a(4) - log_a(2) = log_a(12/2) = log_a(6)

b) 2log a2

2log_a(2) = log_a(2²)

c) -log_a(1/6) - log_a(12)

-log_a(1/6) - log_a(12) = -log_a(12/6) = -log_a(2) = log_a(1/2)

d) log_b(6) + log_b(5) - log_b(2)

log_b(6) + log_b(5) - log_b(2) = log_b(30/2) = log_b(15)
4 5 4
2009-10-05T19:45:08+02:00
A) log a3 + log a4 - log a2 a-podstawa logarytmowana

loga(3) + loga(4) - loga(2) = loga(12/2) = loga(6)

b)

2loga(2) = loga(2²)=loga4

c)-loga(1/6) - loga(12) = -loga(12*1/6) = -loga(2) = loga(1/2)

d) logb(6) + logb(5) - logb(2)

logb(6) + logb(5) - logb(2) = logb(30/2) = logb(15)
2 4 2